Zero Prevalence of Soil-Transmitted Helminth Infections among Students with Disabilities and Symptoms of Attention-Deficit/Hyperactivity Disorder in Bengkulu City, Indonesia - Gunasari, Lala Foresta Valentine; Mufra, Rizki Nurul Hidayah; Sudjatmoko, Andri; Triana, Dessy; Nurmansyah, Dian (CoinReads Media Prima, 2026)
Introduction: Soil-transmitted helminth (STH) infections remain a significant public health concern in Indonesia, particularly among children living in suboptimal sanitation environments. Children with disabilities, especially those exhibiting symptoms of Attention-Deficit/Hyperactivity Disorder (ADHD), are theoretically considered more vulnerable to STH infection because of behavioral factors that may interfere with personal hygiene. However, epidemiological data on STH infections in this population in Bengkulu City are limited. Methods: This descriptive cross-sectional study was conducted among students with disabilities enrolled in special schools (Sekolah Luar Biasa) in Bengkulu. A total of 70 students were selected using proportional stratified random sampling method. ADHD symptoms were assessed using the Indonesian Hyperactive Child Behavior Assessment Scale (SPPAHI), which was completed by parents or guardians. Stool samples were collected and examined for STH infections using the Kato–Katz technique. Results: All 70 stool samples examined were negative for STH infection, indicating a prevalence of zero. Based on the SPPAHI assessment, 56 students (80.0%) were identified as having ADHD symptoms, while 14 students (20.0%) were classified as suspected ADHD. Conclusion: No STH infection was detected among students with disabilities or ADHD symptoms in special schools in Bengkulu City. This zero prevalence may be associated with enhanced parental supervision, limited exposure to high-risk environments, and the effectiveness of the national mass drug administration deworming program in the country.